Design and Construction of Mowing Track for Turfgrass Experimentation in Greenhouses. (1st May 2018) - Braun, Ross C.; Hoyle, Jared A.; Reeves, Jacob A.; Flessner, Michael L.; McElroy, J. Scott
Abstract : Core Ideas: Common hand‐mowing methods can consume large amounts of time in turfgrass greenhouse experiments. There is minimal publication on greenhouse mowing apparatuses for turfgrass research. Utilizing a mowing track can save time and labor compared to greenhouse hand‐mowing methods. A mowing track provides a more uniform height of cut compared to other greenhouse mowing methods. Common hand‐mowing methods require large amounts of time and may not provide a uniform height of cut in turfgrass greenhouse experiments. Greenhouse mowing apparatuses are not uncommon in turfgrass research; however, there is little literature on apparatus specifications. Therefore, a simplified mowing track for turfgrass greenhouse experimentation was designed, built, and tested. An experiment was conducted to examine the differences in mowing time required and mowing uniformity among four greenhouse mowing methods. The amount of time required to set up and mow ranged from 0.74 to 1.18 min m −2 for the mowing track, 6.44 to 6.70 min m −2 with hand shears, 6.82 to 7.49 min m −2 with hedge shears, and 2.95 to 3.37 min m −2 with sheep shears. The mowing track resulted in less variation in height of cut compared to the other tested methods. Overall, a mowing track can save time, labor, and provide a more uniform height of cut compared with other greenhouse mowing methods.